Cryptography Implementation in IP Datagram (International Journal of Engineering and Computer Science, 2013)
The IP packets prepared to sent across the network have a digital signature and public key attached to it which allow to check on each hop along the route to verify the authenticity of packets. For this we use ECC (Elliptic Curve Cryptography). In this paper, we present a software solution of cryptography for PLA (Packet Level Authentication) using the combination of koblitz curves to increase throughput and implicit certificates to decrease storage and computation overhead. A software is developed on open SSL libraries and extending the Open SSL API to support not only fast ECC using Koblitz curves, but implicit certificates and fast signature verifications using implicit certificates as well. Software implementation results of these API extensions are provided, yielding significant speedup of elliptic curve operations.